Interval Training Is Not Superior to Endurance Training With Respect to Bone Accrual of Ovariectomized Mice - Latza, Julia; Otte, Maresa; Lindner, Tobias; Fischer, Dagmar-Christiane; Bruhn, Sven; Hollinski, Robin; Warkentin, Mareike; Mittlmeier, Thomas; Müller-Hilke, Brigitte (Frontiers in Physiology, 2020)
Physical exercise is considered to delay bone loss associated with post-menopausal estrogen deficiency in women. However, the optimal training regimen for maximal bone accrual has not yet been defined. We therefore turned to ovariectomized C57BL/6 mice and directly compared a low intensity endurance training on the treadmill to medium and high intensity interval trainings tailored to the individual performance limits. Trainings lasted 30 minutes each and were performed five times/week. After a five weeks training period, mice were sacrificed and the hind legs analysed for assessment of i) biomechanical stability (three point bending test), ii) for bone microarchitecture (µCT), iii) mineral apposition rate (histomorphometry) and iv) muscle volume (MRI), respectively. Increased running speeds and quadriceps femoris muscle volumes in trained mice confirmed positive impacts on the cardiopulmonary system and myoinduction however, none of the treadmill training regimens prevented ovariectomy induced bone loss. Our results provide evidence that treadmill training impacts differentially on the various members of the musculoskeletal unit and call for further experiments investigating frequency and duration of training regimens.